CHILDFREE PERSPEKTIF TAFSIR AL-MISHBAH: ANALISIS QS. Al-NAHL(16) AYAT 72 - Nur Fajriyani (Jurnal Studi Islam, 2023)
The purpose of this study is to analyze how the concept of childfree is viewed from the approach to the interpretation of the Qur'an in Surat al-Nahl (16) in verse 72 in the interpretation of al-Mishbah. This research is a literature review (literature research). Research with literature review is research that uses library materials as the main data source. In this research, the main data sources are l-Mishbah commentary and articles related to the concept of childfree. Based on the results of the research and discussion, it can be concluded that the concept of childfree is a phenomenon that is very contradictory and not in accordance with the teachings of Islam where economic factors are the reason for being childfree with the assumption that they are unable to fulfill the child's material rights later, or fears of losing a job or disrupting a career that has been built, then things This is very contrary to the motivation of the existing content in QS. al-Nahl: 72 according to the perspective of M. Quraish Shihab, in Tafsir Al Mishbah, that is, Allah made for you wives who are of the same kind as you so that you can get peace of life (Sakinah) from them. And from these wives Allah made for you children and grandchildren.